Analisis Efisiensi Ekonomi dalam Penerapan Aplikasi E-Voting pada Pemilihan Ketua OSIS di SMA/SMK Kab.Grobogan - Ferdianto, Raditya; Damayanti, Adelia Ika; Rahayu, Indah (Universitas YPPI Rembang, 2025)
This study aims to analyze the economic efficiency of implementing e-voting applications in the election of Student Council Chair in SMA/SMK Grobogan Regency.The method employed in this study includes the stages of preparation, socialization, training, implementation, and evaluation.The results of the study indicate positive outcomes, demonstrating that the use of e-voting applications significantly reduces operational costs compared to conventional election methods. The cost savings are attributed to a reduction in the need for ballot paper printing, ink, and logistics, as well as to the time efficiency of the automated vote counting process. Furthermore, e-voting has been shown to increase student participation by facilitating greater accessibility through digital devices.Increased transparency and accuracy in elections has been demonstrated to contribute to public trust in the democratic process within the school environment. Consequently, the implementation of e-voting not only fosters the modernization of the election process, but also provides substantial economic benefits in terms of resource management.This research recommends the wider adoption of e-voting as an innovative step in technology-based democracy.Keywords: E-voting, Economic Efficiency, Student Council Election, Digital Technology, School Democracy